HUBUNGAN PENDIDIKAN ANAK USIA DINI (PAUD) DENGAN PERKEMBANGAN BALITA DI DUSUN GUHA BABAKAN DESA HANDAPHERANG KABUPATEN CIAMIS TAHUN 2017 - Siti Fatimah; Endah Yuli Perwati (Universitas Respati Yogyakarta, 2017)
Abstract. Early childhood is a child aged 3 to 5 years. Age is the most important period in child development. In this stage stimulation is needed to develop the potential of children, one with Early Childhood Education (PAUD) is intended to foster and develop the potential of children from birth to age 5 years. The purpose of this study is to know the relationship of early childhood education (PAUD) with the development of children under five years at Guha Babakan hamlet Handapherang village Ciamis district in 2017. The type of this study is quantitative analytic by using cross sectional approach. In this study, population is all children under five years at GuhaBabakan (hamlet) Handapherang village Ciamis district that is as much52 people/children with sampling technique by total sampling. From calculation by using chi square test, got X2 count= 29.032 with p value 0.000. Then, the valueis interpreted by comparing to chi square critic price got x2 table with df = 2 at 95% confidence interval (5% significance level is 5.991 or p value 0.000 < from 0.05. In conclusion, there is a meaningful relationship between early childhood educationwith the development of children under five years at Guha Babakan Handapherang Ciamis in 2017. PAUD as an educational institution to develop abilities owned by children, also train children to develop fine motor, rough motor, language and socialization. It is expected that parents and families should be able to improve their understanding of the importance of PAUD for the development of children. Keyword: early childhood education (PAUD), children under five years